Evaluation of immunohematology knowledge in hematology trainees. Issue 8 (31st May 2019) - Yan, Matthew T.S.; Arsenault, Valerie; Pendergrast, Jacob
Abstract : BACKGROUND: Canadian hematology trainees are expected to attain clinical knowledge in the subject of red blood cell and platelet antigen systems and the principles of transfusion medicine. However, the relative degree of expertise required in blood bank serology is not well defined. STUDY DESIGN AND METHODS: A modified Delphi approach involving 10 Canadian hematology program directors was utilized to identify 12 relevant topics in immunohematology. A multiple‐choice exam was developed and validated among hematology trainees from 13 hematology training programs across Canada. A Rasch analysis was used to determine fit of the examination before deploying the exam the following year to ascertain the level of knowledge in hematology trainees. RESULTS: The exam was piloted with 62 hematology trainees. The reliability of the exam was 0.93 with a mean item fit score of 1.01. The exam was able to discriminate between training years and self‐rated expertise with better performance attained by more advanced trainees (p < 0.01). No differences were seen between geographic regions. A modified version of the exam was deployed the following year to 85 trainees, with a mean score of 58.9% ± 15.3%. Trainees scored poorest on topics concerning antibody investigations and D variants. CONCLUSION: A standardized exam for assessing hematology trainees on their expected expertise in transfusion immunohematology has been developed and can be used to assess the efficacy of educational resources provided in the subject. Trainees had a low overall mean score indicating additional educational initiatives are warranted.